Varying Heterogeneity among U.S. Firms: Facts and Implications - Chun, Hyunbae; Kim, Jung-Wook; Morck, Randall (The Review of Economics and Statistics, 2011)
U.S. firms' stock return volatility rose fivefold from 1971 through 2000 and then reverted to near 1971 levels by 2006. This was driven mainly by a rise and fall in the firm-specific, rather than systematic, component of volatility. Firm-level total factor productivity growth volatility exhibited a similar pattern. We hypothesize that firm heterogeneity, reflected in firm-specific volatility, rises as a new general purpose technology (GPT) propagates across the economy and then ebbs once the GPT is widespread. Measuring GPT adoption by information technology capital intensity, we find robust cross-industry empirical evidence supporting the hypothesis.